Penerapan Model Discovery Learning untuk Meningkatkan Keterampilan Proses Sains Siswa Sekolah Dasar - Rachmawati, Hani; Fatkhiyani, Kiki (Lembaga Yasin AlSys, 2025)
The research aimed to enhance students' science process skills through the discovery learning model that was conducted in Grade V of UPTD SDN Bangodua 2. The purpose of using the discovery learning model was to increase the range of student activity, focus on the process, encourage self-direction, self-discovery, and frequent reflection as part of the learning activities. Based on initial observational findings, the learning completeness in Natural Science subjects is still very low, with only 30% of students meeting the Minimum Completeness Criteria (Kriteria Ketuntasan Minimum). This was due to the lack of supporting media for science learning and the ineffective learning model applied, resulting in low student engagement in the science learning process. The Classroom Action Research (CAR) method was used in this research. The data collection techniques include interviews, observations, and tests. Data analysis was conducted using average scores in percentage formulas. Based on the research results, student learning outcomes increased to 50% in Cycle 1 and further improved to 80% in Cycle 2.